Waste Matters: Analysing Types and Volumes of Solid Waste in Palawan's Small Island Municipalities for Sustainable Disposal Solutions - Rosario Aynon V, Maria; Gonzales, Arciaga- (Cuestiones de Fisioterapia, 2025)
This study explored the types and volumes of solid waste generated in the small island municipalities of Araceli, Balabac, and Culion in Palawan, Philippines. Using the Waste Analysis and Characterization Study (WACS) approach, combined with data from the Ten-Year Solid Waste Management Plans of the island municipalities, waste from both household and non-household sources including biodegradable, recyclable, and residual materials were analysed. Findings revealed that biodegradable waste constitutes the largest proportion of waste across all study sites, followed by recyclables and residuals. These small islands face unique challenges in waste management due to their geographic isolation, limited access to disposal facilities, and minimal resources for infrastructure. The results aimed to inform local stakeholders and policymakers in implementing waste management strategies as alternatives to traditional landfill disposal as mandated in RA 9003. By establishing a baseline dataset for waste production and composition, this research offers crucial data to support sustainable waste management practices in small island contexts, ultimately aiding in mitigating the environmental impact of increasing waste generation.